2018
DOI: 10.1111/joor.12715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of administration mode on Oro‐facial Appearance assessment using the Oro‐facial Esthetic Scale

Abstract: The administration mode has no significant impact on Oro-facial Appearance assessment when using the OES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…82 However, no significant differences in summary scores between self-administered completion and interviews were observed for OIDP and OES. 80,83 Furthermore, psychometric properties of OHIP and OES did not differ substantially with respect to administration methods. 79,82,83 This indicates all administration methods are a valid approach to assess OHRQoL, but applying different modes of administration within a particular study should be avoided or when performed accompanied by evidence of no influence of the administration method on research question.…”
Section: Methods Of Ohrqol Instrument Administrationmentioning
confidence: 94%
See 1 more Smart Citation
“…82 However, no significant differences in summary scores between self-administered completion and interviews were observed for OIDP and OES. 80,83 Furthermore, psychometric properties of OHIP and OES did not differ substantially with respect to administration methods. 79,82,83 This indicates all administration methods are a valid approach to assess OHRQoL, but applying different modes of administration within a particular study should be avoided or when performed accompanied by evidence of no influence of the administration method on research question.…”
Section: Methods Of Ohrqol Instrument Administrationmentioning
confidence: 94%
“…While all studies revealed OHIP summary scores were higher for self‐administered questionnaires than for any form of interview, this effect was not statistically significant and not clinically relevant in prosthodontic patients 79 and in primary dental care patients 80,81 but were in patients with chronic periodontitis 82 . However, no significant differences in summary scores between self‐administered completion and interviews were observed for OIDP and OES 80,83 . Furthermore, psychometric properties of OHIP and OES did not differ substantially with respect to administration methods 79,82,83 .…”
Section: How To Administer An Ohrqol Instrument?mentioning
confidence: 91%
“…In the current study, the questionnaires were distributed either in hard or electronic form. Neophytou et al [33] reported no impact of administration mode on the assessment of orofacial appearance using the OES. https://doi.org/10.1371/journal.pone.0239232.t004 Table 5.…”
Section: Plos Onementioning
confidence: 99%